Atomistic modeling and dynamic analysis of boron nitride nanotube in the presence of hexagonal defect. (2020) - Sharma, Harsh; Shrivastava, Sharad; Rathore, Jitendra S.; Trivedi, Sandesh
Abstract: The feasibility of defective Single-Walled Boron Nitride Nanotube (SW-BNNT) has been explored in the present paper employing finite element based three-dimensional atomistic modeling approach. The effect of missing of three conjugate BN pairs in SW-BNNT resulting in formation of hexagonal defect in SW-BNNT on resonance frequency has been analyzed in the present paper. Two different types of SW-BNNT i.e., armchair (5, 5) and Zigzag (5, 0) BNNT of 5 nm length have been analyzed for cantilever and bridged configuration. Further, present work explores the effect of position of defect on resonance frequency in SW-BNNT. The simulation results revels that resonance frequency decreases due to presence of defect and this reduction in frequency increases if the position of defect moves towards free end in the case of cantilever configuration. On the contrary for bridge configuration the resonance frequency decreases continuously if position of defect moves from fixed end to midpoint. Thus it can be concluded that due to presence of defect in nanotube, the resonance frequency decreases and suggests that stiffness is more dominating than mass of nanotube.